ANALYSIS OF THE IMPACT OF THE PERCEPTION OF THE QUALITY OF CAR INSURANCE SERVICE ON THE ACT OF TERMINATION INITIATED BY POLICYHOLDERS ON EXPIRY - ROUAINE, Zakaria (Revue Internationale du Chercheur, 2023)
Actuarial calculations and probabilistic analyses of insurance operations have proven over time to be caught between retention, multiple risk exposures and most importantly massive changes in customer behaviour. Nowadays, customers are much more vigilant and expect a lot from their insurers and it is recognized today that the analysis of their behaviour is certainly a primordial matter in decision making, being one of the main challenges taken up by insurance companies in order to promise and establish their sustainability in the long run. This article will attempt to analyse the impact of direct (the insured's perception of the quality of the insurance service offered) and indirect (the involvement of the insured, the commitment of the provider to its insured, the cost of changing the insurer, and the alternatives in the insurance market) determinants on the act of cancelling motor insurance contracts initiated by the insured at the end of the contract in the Rabat area. The study will use a sample of 550 policyholders and will employ generalized linear models, more specifically, binary logistic regression.